Control of ATP homeostasis during the respiro‐fermentative transition in yeast - Thomas Walther; Maite Novo; Katrin Rössger; Fabien Létisse; Marie‐Odile Loret; Jean‐Charles Portais; Jean‐Marie François (Molecular Systems Biology)
Abstract Respiring Saccharomyces cerevisiae cells respond to a sudden increase in glucose concentration by a pronounced drop of their adenine nucleotide content ([ATP]+[ADP]+[AMP]=[AXP]). The unknown fate of ‘lost’ AXP nucleotides represented a long‐standing problem for the understanding of the yeast's physiological response to changing growth conditions. Transient accumulation of the purine salvage pathway intermediate, inosine, accounted for the apparent loss of adenine nucleotides. Conversion of AXPs into inosine was facilitated by AMP deaminase, Amd1, and IMP‐specific 5′‐nucleotidase, Isn1. Inosine recycling into the AXP pool was facilitated by purine nucleoside phosphorylase, Pnp1, and joint action of the phosphoribosyltransferases, Hpt1 and Xpt1. Analysis of changes in 24 intracellular metabolite pools during the respiro‐fermentative growth transition in wild‐type, amd1, isn1, and pnp1 strains revealed that only the amd1 mutant exhibited significant deviations from the wild‐type behavior. Moreover, mutants that were blocked in inosine production exhibited delayed growth acceleration after glucose addition. It is proposed that interconversion of adenine nucleotides and inosine facilitates rapid and energy‐cost efficient adaptation of the AXP pool size to changing environmental conditions.